Design and development of a human height measurement system for sports health screening - M. Rodzi, Nurul Jannah; Abd Wahab, Hanani (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The rapid development of the Internet of Things (IoT) has enabled the creation of innovative and effective health monitoring systems. In the field of sports, height is an important physical characteristic that is important data in physical fitness standard tests and sports centre were taken during the screening session. However, traditional methods of measuring height can be time-consuming and extend the process flows. The development and design of a human height measurement system with IoT-based monitoring for sports health screening help to read the human height measurement from a distance. The circuit design consists of a NodeMCU ESP32 Wi-Fi Modules, HC-SR04 Ultrasonic Distance Sensor, LED Dot Matrix (MAX7219), and a cloud-based database. The height sensor as known as HC-SR04 Ultrasonic Distance Sensor at human height measurement prototype is mounted on a wall, and the ESP32 is connected to the computer via a USB serial connection and will be used as a gateway to retrieve data from the sensors ESP32 will transfer the data to Arduino IDE (serial monitor) and Blynk will be able to retrieve the data from that and display on the dashboard or gauge using a smartphone. The proposed system is a cost-effective and efficient way to measure height for sports health screening. The system is also scalable and can be easily adapted to different settings.